Feasibility and outcome of CT-guided lung biopsy in patients with hematological diseases and suspected fungal pneumonia - Sharma, Sanjeev Kumar; Kumar, Suman; Singh, Avinash Kumar; Seth, Tulika; Mishra, Pravas; Mahapatra, Manoranjan; Sharma, Sanjay; Tyagi, Seema; Xess, Immaculata; Ray, Ruma (The Journal of Infection in Developing Countries, 2013)
Introduction: Fungal pneumonia is a major cause of morbidity and mortality in immunocompromised patients with hematological diseases. This study is aimed to evaluate the feasibility and outcome of computed tomography (CT) guided lung biopsy or fine needle aspiration cytology (FNAC) in the diagnosis of fungal pneumonia in patients with hematological diseases. Methodology: Seven hundred and seventy six consecutive patients with febrile neutropenia were evaluated prospectively over the period of three years. Patients with suspected fungal pneumonia, based on typical CT scan findings, were considered for lung biopsy. Results: Of the 776 patients evaluated for fever, 235 (30.3%) showed CT scan findings consistent with fungal pneumonia. Of the 235 patients, CT-guided lung biopsy/FNAC was recommended for 178 patients but could be performed in only 34 (19.1%) patients. Fungal pneumonia was proven in 15 (44%) out of 34 patients (aspergillus in 12; mucormycosis in 3 patients). Lung biopsies could not be performed for a number of reasons. These included thrombocytopenia, nodules being too small, infection improving with empiric treatment and patient recovering clinically, and the patient being too sick to undergo intervention. The median absolute neutrophil count (ANC) of patients at the time of lung biopsy was 0.41x109/l in patients whose lung biopsy/FNAC showed fungal pneumonia, compared to 2.10x109/l in patients whose biopsy/FNAC showed necrotizing pneumonitis. Conclusion: CT-guided lung biopsy/FNAC can allow the definitive diagnosis of fungal pneumonia in selected patients with various hematological diseases and should be attempted whenever clinically indicated and radiologically feasible.